Pavement performance assessment using a cost‐effective wireless accelerometer system. (26th February 2020) - Bajwa, Ravneet; Coleri, Erdem; Rajagopal, Ram; Varaiya, Pravin; Flores, Christopher
Abstract: Pavement condition monitoring is required to identify pavements in need of maintenance or rehabilitation. Early identification of reduction in pavement's structural resistance and improving the structural resistance by minor repairs can lead to significantly lower maintenance costs for transportation agencies. In this study, a cost‐effective wireless sensor that can be embedded in the road to measure the transient vibrations due to different applied loads was tested to determine its effectiveness in terms of pavement displacement measurements. Test results show that the vibration sensor, combined with the algorithms, can be embedded in new or existing pavements and used as an accurate wireless displacement sensor. The low cost of the sensor system allows the use of these sensors at high densities for monitoring the performance of an entire road network. Outputs from the developed system can be directly used to evaluate the condition and performance of pavement structure (increasing displacement over time indicating increasing pavement damage). In addition, displacement data from the system can be used to backcalculate pavement layer stiffnesses, which can be used to predict long‐term performance of the pavement structure. Reduction in pavement layer stiffness over time can be used to determine long‐term damage accumulation.